Expanding contraceptive choice among first-time mothers age 15–24 in Kinshasa: The Momentum pilot project - Gage, Anastasia J.; Wood, Francine Eva; Gay, Rianne (Frontiers in Global Women's Health, 2023)
Evidence shows that an expanded range of contraceptive methods, client-centered comprehensive counseling, and voluntary informed choice are key components of successful family planning programs. This study assessed the effect of the Momentum project in expanding contraceptive choice among first-time mothers (FTMs) age 15-24 who were six-months pregnant at baseline in Kinshasa, Democratic Republic of the Congo, and socioeconomic determinants of the use of long-acting reversible contraception (LARC). The study employed a quasi-experimental design, with three intervention health zones and three comparison health zones. Trained nursing students followed FTMs for 16 months and conducted monthly group education sessions and home visits consisting of counseling and provision of a range of contraceptive methods and referrals. Data were collected in 2018 and 2020 through interviewer-administered questionnaires. The effect of the project on contraceptive choice was estimated using intention-to-treat and dose-response analyses, with inverse probability weighting among 761 modern contraceptive users. Logistic regression analysis was used to examine predictors of LARC use. Project effect was detected on receipt of family planning counseling, obtaining the current contraceptive method from a community-based health worker, informed choice, and current use of implants versus other modern methods. There were significant dose-response associations of the level of exposure to Momentum interventions and the number of home visits with four of five outcomes. Positive predictors of LARC use included exposure to Momentum interventions, receipt of prenatal counseling on both birth spacing and family planning (age 15-19), and knowledge of LARCs (age 20-24). The FTM’s perceived ability to ask her husband/male partner to use a condom was a negative predictor of LARC use. Given limited resources, expanding community-based contraceptive counseling and distribution through trained nursing students may expand family planning access and informed choice among first-time mothers.